Are All Forms of Blood Clotting a Result of Vitamin D Deficiency? A Hypothesis and Short Review - Gelbard, Amos (British Journal of Healthcare and Medical Research, 2025)
In a previous study I showed low levels of Vitamin D correlate not only with the occurrence of Ischemic Stroke but also with a rise in Parathyroid Hormone (PTH) secretion. This hormone is responsible for transference of Calcium from the bones to the blood stream which as I explained is a result of Vitamin D deficiency, this I hypothesized could be causing the blood clot leading to the aneurism in Stroke. Herein I take this hypothesis a step further and suggest that all forms of blood clotting could perhaps be traced back to the calcification of the blood stream caused by PTH because of Vitamin D deficiency. I will bring forward a few studies that all share the observation of Vitamin D deficiency in non-stroke life threatening blood clotting like Deep Vein Thrombosis, Venous Thrombosis and Pulmonary Embolism. I will raise the need to further examine this connection between Vitamin D levels and Thrombosis, as a possible preventive and perhaps therapeutic.